PENGARUH MODEL PEMBELAJARAN PARTISIPATIF MENGGUNAKAN METODE PEMECAHAN MASALAH TERHADAP HASIL BELAJAR FISIKA SISWA KELAS VIII SMPN 3 BATUKLIANG - Kusumawati, A.; Kosim, Kosim; Gunawan, Gunawan (Lensa : Jurnal Kependidikan Fisika, 2013)
This study is an experimental study that aims to knows the influence of participative learning model used problem solving methode towards learning physics achievement of studens in SMPN 3 Batukliang. Research design using pre-test - post-test control group design. Sampling using random cluster sampling, the students of class VIII-A as the experimental group and the students of class VIII-B as a control group. The learning physics achievement data of students were analyzed using t-test formula two parties polled variance. At the significant level of 5% and dk of 53 obtained that ttest is less than ttable (1.66< 2.007). Because  that ttest is less than ttable  therefore H0 is accepted and Ha is rejected. Therefore, it can be  concluded that the participative learning model used problem solving methode is not influential significantly towards learning physics achievement of studens in SMPN 3 Batukliang.